Hazard Rating of Substances Systems Developed by Niosh’s Rtecs-Nohs and Usepa - Law, P.L; Michael J., Ellenbecker; Ng, Chee Khoon (The Institution of Engineers, Malaysia, 2006)
This research study attempts to evaluate the hazard rating of substances systems developed by NIOSH’s (National Institute for Occupational Safety and Health) RTECS-NOHS (Registry of Toxic Effects of Chemical Substances – National Occupational Hazards Survey) and USEPA (United States Environmental Protection Agency). Evaluation on rating methodologies and parameters used by both NIOSH and USEPA’s systems reviewed that both systems aim at ranking common industrial organic compounds used or released into the atmosphere with special focus on chemical toxicological health effects. The NIOSH’s RTECS-NOHS system solely emphasizes on health risks depending on chemical toxicological effects pertaining to eight health effect endpoints, whilst USEPA’s system considers toxicological effects, occupational standards, chemical production rate, fraction of production loss and chemical’s volatility characteristics. It is also found that NIOSH’s system allows users great flexibility in defining toxicological priorities by assigning a multiplier or/and adding in the constants. The scoring system developed by USEPA for the individual parameters considered in the priority ranking range from zero to five without providing flexibility for users in defining toxicological priorities or assigning multipliers. It is also found that certain modifications must be made to account for fundamental differences between worker and population exposures for application purposes.